Energy efficiency applied to electricity consumption: A bibliographic review study (Research, Society and Development, 2021)
The growing demand for electricity has been stimulating studies and actions not only to increase the generation capacity of plants, but also the rational use of this important form of energy. As a result, there is a notable growth in the number of publications related to the theme, thus generating too many works, which makes filtering and analysis complex. In this context, the bibliographic review is an important tool for quantitative and qualitative verification of studies published in different journals. Given the above, this article aims to perform a bibliometric analysis of Brazilian scientific production on energy efficiency applied to electricity consumption. The Scopus database was used to search for articles related to the topic. A total of 66 papers were found in the period from 2004 to 2020, however, after a dynamic reading it was found that only 37 of them effectively talk about energy efficiency linked to electricity consumption. Of these, 83.8% correspond to case study works, 10.8% to public policies and 5.4% were literature review studies. The analysis showed that most of the case study articles were applied to the industrial sector (45.2%), especially to the driving systems. In addition, it was observed that even though the residential sector is one of the main consumers of energy, there is a small number of publications, thus indicating a gap to be filled.